Dose response of three-dimensional silicone-based radiochromic dosimeters for photon irradiation in the presence of a magnetic field. (October 2020) - Jensen, Morten B.; Balling, Peter; Doran, Simon J.; Petersen, Jørgen B.B.; Wahlstedt, Isak H.; Muren, Ludvig P.
Abstract: The magnetic field in magnetic resonance imaging guided radiotherapy (MRgRT) delivery systems influences charged-particle trajectories and hence the three-dimensional (3D) radiation dose distributions. This study investigated the dose-response as well as dose-rate and fractionation dependencies of silicone-based 3D radiochromic dosimeters for photon irradiation in a magnetic field using a 0.35 T MRgRT system. We found a linear dose response up to 22.6 Gy and no significant dose-rate dependency as a function of depth. A difference in optical response was observed for dosimeters irradiated in a single compared to multiple fractions. The dosimeter showed clinical potential for verification of MRgRT delivery.